Methods of Teaching Engineering Sciences on the Subject of "Tape Transmissions" (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Enter. Since the first years of independence of the Republic of Uzbekistan, special attention has been paid to the improvement of the field of education.During a historically short period of time, great work has been done in this field in our country, and even today, work in this field is being continued intensively.